Recent settlement trends in Panulirus argus (Decapoda: Palinuridae) pueruli around St. Thomas, U.S. Virgin Islands - Kojis, B. L. (2003)
Puerulus settlement of the western Atlantic spiny lobster, Panulirus argus, was monitored using modified Witham collectors from December 1996 to March 1998 at seven sites around St. Thomas, U.S. Virgin Islands. A total of 605 pueruli were collected from 553 samples for a catch per unit effort (CPUE) for all sites of 1.09 pueruli. The greatest settlement occurred on sites within a recently declared marine reserve, which had an overall CPUE of 1.77 pueruli. Settlement in non-reserve sites was much lower with an overall CPUE of 0.31 pueruli. Pueruli recruitment declined 67% at inshore sites and 53% at offshore sites between July 1992 - April 1994 and February 1997 - March 1998. Also, only 10% of months sampled in 1997-98 had a CPUE > 0.5 compared to 55% in a previous study in 1992 - 1993. Despite the decline in pueruli CPUE in 1997-98 compared to 1992-94, the commercial lobster catch in the 2000-01 fishing season, and by inference the adult lobster population (legal lobster size in the US Virgin Islands is ≥ 3.5 cm carapace length), remained stable.